KINETICS OF METHYLENE BLUE ADSORPTIONON KOH-ACTIVATED CARBON USING CORN COBS - Basheer Hasan, Diya’uddeen; I.A, Mohammed; B.Y, Jibril (Malaysian Journal of Science, 2011)
Different samples of activated carbons were prepared by carbonization of corn cob – an abundant lignocelluloses material available locally. The thermo-gravimetric profile of the carbon was studied. Based on this, carbonization temperature was varied (600 – 800 oC) to obtain samples of different surface areas, porosities and densities. The sample carbonized at 700 oC exhibited the highest surface area and apparent density of 1,084 m2 /g and 0.1031 g/cm2 . These characteristics were associated with the extent of re-polymerization reactions of the tar species with the main carbon matrix at the reaction temperature. The samples were further compared based on the adsorption of methylene blue (MB) from its aqueous solution. The adsorption was investigated using MB initial concentrations of 100-500 mg/L at ambient temperature of 30 oC, constant pH, adsorbent dosage and particle size. Equilibrium isotherms generated were analyzed according to the linear form of Langmuir and Freundlich isotherms. The Langmuir model was found to better describe the adsorption process over the whole concentration range. The adsorptive capacities range for the model is 417 – 833 mg/g. Attempt was made to find the adsorption mechanism. Both pseudo-first-order model and pseudo-second-order kinetic model were tested. Better description was found using pseudo-second-order model. The study demonstrated that locally available carbonaceous materials could be employed to prepare activated carbon with high adsorptive capacity. (Keywords: Activated carbon; Adsorption isotherm; Corn cobs; Kinetics; Methylene blue)